Economic Exposure and Crisis Resilience in Exogenous Shock: The Short-Term Economic Impact of the Covid-19 Pandemic in the EU - Czeczeli, Vivien; Kolozsi, Pál Péter; Kutasi, Gábor; Marton, Ádám (Public Finance Quarterly, 2020)
The coronavirus epidemic arrived in Europe in the spring of 2020, causing a significant slowdown in economic activity. The study examines the preparedness, vulnerability, exposure and performance of 25 European countries during the economic crisis caused by the Covid-19 epidemic. Countries can be divided into seven groups with the cluster analysis executed during the research, based on fiscal, social, and external vulnerability indicators. Specific patterns of country groups are explored in the value and evolution of crisis period indicators of production, labor market, mobility and risk premium. The aim of the analysis is to find a correlation between pre-crisis preparedness and the extent of the economic shock caused by the crisis. The research divided the countries into seven groups based on their fiscal and social stance and external vulnerability. Then, specific patterns of country groups are explored in the value and evolution of production, labour market, mobility and risk premium indicators during the crisis. The analysis concludes that a clear link can be established merely between the state of public finances and the indicator of financial risk in the examination of the behaviour of clusters. For all clusters, it was confirmed that the decline in mobility was mostly accompanied by a slowdown in industrial production, but not by unemployment, which may indicate the impact of economic policy measures aimed at maintaining jobs. The results support the initial theoretical assumption that in an economic crisis caused by a exogenous shock originated in non-economic factor, the explanatory power in terms of short-term effects is much lower than in crises caused by economic risks.